Formulasi dan Evaluasi Sediaan Sabun Mandi Cair Menggunakan Sari Buah Bit (Beta Vulgaris L.) Sebagai Pelembab Kulit - Devina Chandra; Natanael Priltius; Betharina Br Tarigan (The Journal General Health and Pharmaceutical Sciences Research, 2024)
Liquid bath soap is a liquid preparation used to clean the skin, made from soap base ingredients with added surfactants, foam stabilizers and fragrances, which is used when bathing without irritating to the skin. Liquid bath soap is made by saponifying oil and fat with KOH. Quality soap must have high detergent power, can be used on various types of materials and remain effective at different temperatures and water levels. In this study, this liquid bath soap used the addition of beetroot juice which is rich in benefits for skin health. The aim of this research is to find out whether beetroot juice formulated into liquid bath soap will have a moisturizing effect on the skin, and determine the concentration of beetroot juice as the best skin moisturizer. This research is made into four formulas. First without the addition of F0 Beetroot Juice (0%), Second with the addition of F1 Beetroot Juice (10%), Third with the addition of F2 Beetroot Juice (15%), Fourth with the addition of F3 Beetroot Juice (20%). From the results of this research, we got good results in the liquid bath soap formulation with the addition of 20% beetroot juice (F3), and from the results, the F3 formulation (20%) was also the most preferred by the panelists for the aroma and color of the fruit juice liquid bath soap beet.